The Mediating Role of Growth in the Relationship Between Capital Adequacy, Asset Quality, Liquidity, and Dividend Payout Policy - Gunawan, Nurani Cahya; Yusnita, Irni (ADPEBI Publisher, 2026)
Purpose – This paper aims to analyze the influence of Capital Adequacy Ratio (CAR), Non-Performing Loan (NPL), and Loan to Deposit Ratio (LDR) on Dividend Payout Ratio (DPR), with Growth as a mediating variable, using data from Indonesian state-owned banks over the period of 2015–2024. Methodology/approach – The research employs a quantitative approach using secondary data from financial reports of state-owned banks. Panel data regression analysis is applied to examine the direct and indirect relationships among CAR, NPL, LDR, Growth, and DPR. Findings – The results show that CAR and Growth have a significant positive effect on DPR. NPL has a significant negative effect on both Growth and DPR. LDR has a negative effect on DPR but a positive effect on Growth. Growth significantly mediates the relationship between CAR, NPL, LDR, and DPR. Novelty/value – This study provides empirical evidence on how internal financial ratios and growth influence dividend policy in Indonesian state-owned banks. It highlights the mediating role of Growth in strengthening the link between financial performance and dividend payout, offering strategic insights for bank management and policymakers in improving dividend policy frameworks.